Dorothea Lange : a life beyond limits - Gordon, Linda (London ; New York : W.W. Norton & Co., 2009)
Dorothea Lange's photographs define how the American Depression is remembered; this evocative biography defines her creative struggles and enduring legacy.
"A camera is a tool for learning how to see--" -- Hoboken and San Francisco, 1895-1931. Child of iron, wounded ; Apprentice to the city ; Becoming a photographer ; Maynard Dixon, Bohemian artist ; Working mother in Bohemia -- Depression and renewal, 1932-1935. Leaving the children, leaving the studio ; A New Deal for artists ; Paul Schuster Taylor, maverick economist ; The romance of love, the romance of the cause ; Blending a family -- Creating documentary photography, 1935-1939. Father Stryker and the beloved community ; On the road : California ; Migrant Mother ; On the road : the Dust Bowl ; On the road : the South ; An American Exodus ; Dorothea and Roy -- Wartime, 1939-1945. Family stress ; Defiant war photography : the Japanese internment ; Unruly war photography : the Office of War Information and Defense Workers -- Independent photographer, 1945-1965. Surviving in the cold ; Working for Life ; Diplomat's wife ; To a cabin ; Photographer of democracy -- Lange's photograph captions.
Includes bibliographical references and index.
Keywords: Lange, Dorothea; Photographers -- United States -- Biography; Documentary photography -- United States -- History -- 20th century; United States -- Social life and customs -- 20th century -- Pictorial works